Evaluasi Program Yustisi Kebersihan di Kota Banjarmasin - Syafari, Muhammad Riduansyah (Fakultas Ilmu Sosial Universitas Negeri Padang, 2012)
This article will discuss the finding research about the evaluation of the justice sanitation program in Banjarmasin. This research is conducted to find out the effectiveness of the program which is analysed in the achievement of the goals in terms of its output and outcome. The approach used in this research is descriptive qualitative and the formal evaluation, with the evaluation technique analysis is single program after only. The result shows that: output and outcome program is not reached/ ineffective